Diamond grinder for roughness measurement extends pavement service life - Wong, Bing (2025)
Concrete pavements wear down, crack, or develop slab step-offs over time. To restore the pavement surface, diamond grinding offers several advantages: lower cost compared to an overlay, improved safety by increasing surface texture, and minimal traffic disruption during repairs.